IMMUNO-INFLAMATORY RESPONSES IN ACUTE CORONARY SYNDROME - R. G. Oganov; N. E. Zakirova; A. N. Zakirova; G. M. Salakhova; M. R. Plotnikova (Столичная издательская компания, 2015)
Aim. To determine the role of immuno-inflammatory responses in the development of acute coronary syndrome (ACS).Material and methods. 93 patients with acute coronary syndrome (ACS), including 60 patients with unstable angina (UA) and 33 patients with acute myocardial infarction (AMI) were involved in the study. Comparison group included 83 patients with stable angina and control group - 25 healthy persons. The diagnosis of ischemic heart disease (IHD) was verified on the basis of clinical and instrumental data. For assessment of immuno-inflammatory responses levels of C-reactive protein (CRP), pro-inflammatory (interleukins [IL-1β, IL-6], tumor necrosis factor [TNF-α]) and anti-inflammatory (IL-4, IL-10) cytokines we determined by ELISA method.Results. There were high levels of pro-inflammatory cytokines (IL-1β, IL-6, TNF-α), high CRP level and low levels of anti-inflammatory IL-4, IL-10 cytokines in UA and AMI patients. Insignificant immunological shifts were found in stable angina patients.Conclusion. Destabilization in the IHD course is characterized with more active immuno-inflammatory responses. Activity of these reactions is associated with ACS severity.